Sustainable Economics Education Curriculum as An Effort to Increase Fiscal Incentives for Sustainable Investment - Maqsudi, Achmad (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Sustainable economic education (PEB) is an important aspect of creating understanding and awareness of the challenges and opportunities faced by society in the context of sustainability. This article explores the relationship between the PEB curriculum and efforts to increase fiscal incentives for sustainable investment. This research aims to identify and analyze the impact of the PEB curriculum on public understanding and support for fiscal incentives for sustainable investment. This research used a qualitative approach. The source of data in this study was obtained from interviews and official documents. The interview will be recorded to document the information more accurately. Document analysis was carried out by identifying the main findings related to the PEB curriculum and fiscal incentives. Qualitative data from interviews will be analyzed using a thematic approach. Data from document analysis will be compiled and analyzed to support interview findings. The results of the analysis show that exposure to PEB material that incorporates sustainable investment concepts can increase the level of public awareness of the importance of sustainability aspects in the economic context. This has the potential to increase public support for fiscal incentive policies aimed at encouraging sustainable investment.